Training to self-care: fitness tracking, biopedagogy and the healthy consumer. - Fotopoulou, Aristea; O'Riordan, Kate (Health Sociology Review, 2017)
In this article, we provide an account of Fitbit, a wearable sensor device, using two complementary analytical approaches: auto-ethnography and media analysis. Drawing on the concept of biopedagogy, which describes the processes of learning and training bodies how to live, we focus on how users learn to self-care with wearable technologies through a series of micropractices that involve processes of mediation and the sharing of their own data via social networking. Our discussion is oriented towards four areas of analysis: data subjectivity and sociality; making meaning; time and productivity and brand identity. We articulate how these micropractices of knowing one's body regulate the contemporary 'fit' and healthy subject, and mediate expertise about health, behaviour and data subjectivity.